(untitled) (Journal of Hama University, 2026)
This research aims to study the impact of financial flexibility on the returns of Islamic banks operating in Syria during the period 2011–2023 The study used return on equity and return on unrestricted investment account holders’ equity as dependent variables. Cash holdings, financial leverage, and liquidity are included as independent variables, with bank size used as a control variable. The study used cross-sectional time series (Balanced Panel data) and applied the ARDL model using the Pooled Mean Group (PMG) method. The study found no significant effect of financial flexibility, as measured by its three indicators, on return on equity. Furthermore, there was no significant effect of financial flexibility, as measured by financial leverage, on return on unrestricted investment accounts holders’ equity. However, the study found a significant negative effect of financial flexibility, as measured by liquidity and cash holdings, on return on investment account holders’ equity. In light of the results, the study offers a set of recommendations, such as the necessity for Islamic banks operating in Syria to consider financial flexibility indicators and their impact on the bank’s financial performance, as measured by return on equity and return on unrestricted investment account holders’ equity.